IMPLEMENTASI SISTEM PAKAR DALAM MENDIAGNOSIS PENYAKIT PNEUMONIA PADA ANAK - Yenni, Yusli; Khaerini, Nini (Jurnal Liga Ilmu Serantau, 2025)
Pneumonia is a disease with a high mortality rate in children. Pneumonia is an acute respiratory infection and is a disease that is often suffered by children and remains a high cause of child mortality in Indonesia. This occurs due to the still limited knowledge of parents and the lack of medical personnel and treatment facilities, especially in certain areas. This becomes a major point causing delays in disease treatment, resulting in death in children. This research aims to develop and implement a rule-based expert system. Knowledge can assist in the process of diagnosing pneumonia in children. This expert system knowledge is a system that can solve a problem by using the mindset of an expert implemented into the system. This system is built using the forward chaining method in diagnosing pneumonia. The forward chaining method is known as data-driven reasoning because this method searches starting from data or facts that are already known as input. It also searches for appropriate rules, then decisions can be made based on the rules that have been created. The interface implementation uses a web-based system using the PHP programming language and a MySQL database, which can be accessed by the public for consultation. It is hoped that this system will assist relevant parties, especially those with limited knowledge of pneumonia. It will also help medical professionals and the government reduce the child mortality rate due to this disease.